Syphilis Self-Testing Among Female Sex Workers in China: Implications for Expanding Syphilis Screening - Wang, Cheng; Li, Xia; Wang, Yajie; Yang, Bin (Frontiers in Public Health, 2022)
Background: Syphilis self-testing (SST) may help expand syphilis test uptake among female sex workers. However, there has been no studies on examining SST among female sex workers. We aim to examine SST experience and its determinants among female sex workers in China. Methods: A venue-based, cross-sectional study of female sex workers was conducted in eight Chinese cities in 2019. Participants completed a survey including socio-demographic characteristics, sexual behaviors, and SST history. Multivariable logistic regression was conducted to evaluate the associated factors with SST. Results: Among 1287 Chinese female sex workers, 72.1% (928/1287) had ever tested for syphilis, and 5.9% (76/1287) had ever used syphilis self-testing. Among syphilis self-testers, more than half (57.9%, 44/76) reported that the self-test was their first syphilis test, around one-fifth (18.4%, 14/76) reported that syphilis self-testing results influenced the price of commercial sex. After adjusting for covariates, female sex workers who received anal sex in the past month (adjusted odds ratio [aOR]: 2.6, 95%CI: 1.5-4.3), used drugs before or during sex (aOR: 3.8, 95%CI: 2.3-6.4), tested for other sexually transmitted infections (STIs) in the past 6 months (aOR: 3.4, 95%CI: 1.9-6.0), ever tested in the hospital (aOR: 5.1, 95%CI: 2.5-10.4), and ever tested in the community (aOR: 1.7, 95%CI: 1.3-2.2) were more likely to perform syphilis self-testing. Conclusions: Syphilis self-testing has the potential to expand testing coverage, and increase testing frequency with limited potential harms among FSW. Further evaluation on the intervention effects based on syphilis self-testing among FSW are needed.